Comparative Characterization of Saltwater from Kula, Nembe, and Kwale in the Niger Delta, Nigeria (Global Journals of Research in Engineering, 2024)
Three samples of water from Kwale Nembe and Kula in the Niger Delta were collected and characterized and the following properties pH Temperature Dissolved Oxygen Turbidity Acidity Alkalinity Electrical conductivity Salinity Oil and Grease Total Hydrocarbon THC Heavy metals BTEX and Poly Aromatic Hydrocarbon PAH were determined The result of some of the key parameters showed that the Salinity of the Kula water sample is highest with a salt concentration of 13 115mg L at 30 C followed by the Nembe water sample with a salt concentration of 2 500mg L at 29 68 C and Kwale with a small salt concentration of 60mg L at 28 67 C The electrical conductivity of the three water samples followed the same trend as salinity with Kula Nembe and Kwale water samples having electric conductivity of 20 101 S cm at 30 C 1 489 S cm at 29 68 C and 122 S cm at 28 67 C respectively The Polimomatric hydrocarbon content in the three water samples showed that the Nembe water sample has the highest polimomatric hydrocarbon of 0 969mg L followed by the Kwale water sample with 0 705mg L and Kula water sample with 0 229mg L Interestingly the results also showed that n-pentacosane concentration is the highest component of the Total Petroleum Hydrocarbon TPH in the Kula and Kwale samples while n-hexacosane concentration is the highest component of the TPH in the Nembe water sample This explains why the Nembe water sample is cloudier than the Kwale and Kula water samples But in BTEX composition the total BTEX is highest in Nembe water followed by Kwale and the least of these components is in Kula water
Keywords: characterization; seawater; physiochemical and heavy metal; polyaromatic hydrocarbon; total petroleum hydrocarbon; BTEX